EDUKASI PEMAHAMAN THAHARAH DALAM KEHIDUPAN SEHARI-HARI PADA PERWIRITAN NURUL HIDAYAH HUTA TALUN KONDOT PANOMBEAN PANE SIMALUNGUN - Muhammaz Zein; Mely Novasari Harahap (MADANI PUBLISHER INDONESIA, 2025)
The purpose of this Taharah education and practice is to help the congregation of the Nurul Hidayah Huta Talon Kondot Panombean Pane Simalungun community understand the material related to Taharah and the procedures for performing Taharah in their daily lives, in accordance with the teachings of the Prophet Muhammad (peace be upon him). The practical implementation is intended to enable the congregation to directly understand how to perform Taharah properly and correctly. The work program that has been prepared includes several methods for its implementation. These methods include training and outreach related to Taharah education for the congregation of the Nurul Hidayah Huta Talon Kondot Panombean Pane Simalungun community. The results of this educational program on understanding Taharah among the congregation of the Nurul Hidayah Huta Talon Kondot Panombean Pane Simalungun community show that all congregants can effectively follow the Taharah practices. This indicates that they have understood the Taharah procedures.